2014
DOI: 10.1016/j.jcrs.2013.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic study of the cornea by in vivo confocal microscopy and optical coherence tomography after bifocal refractive corneal inlay implantation

Abstract: Dr. M. Fantozzi is a member of the Presbia medical advisory board. No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In the creation of intrastromal ring tunnels, Kamburoglu et al [16] observed that the resection created by FSL was deeper by 6.5-69 lm in a Scheimpflug camera observation. Recent assessment with AS-OCT showed that FSL resections with an intended depth of 300 lm were created at 292 ± 10 lm [17]. In the current case series, the mean incision depth was deeper by 60 lm.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In the creation of intrastromal ring tunnels, Kamburoglu et al [16] observed that the resection created by FSL was deeper by 6.5-69 lm in a Scheimpflug camera observation. Recent assessment with AS-OCT showed that FSL resections with an intended depth of 300 lm were created at 292 ± 10 lm [17]. In the current case series, the mean incision depth was deeper by 60 lm.…”
Section: Discussionmentioning
confidence: 50%
“…The technology has been used to create LASIK corneal flaps [4], corneal tunnels for intrastromal rings [16,17], and grafts for PKP [5]. Accurate incisions were anticipated for the FSL-assisted AK incisions.…”
Section: Discussionmentioning
confidence: 99%
“…When the inlay is removed, the patient’s visual acuity returns to ranges comparable to the preoperative state 11,15,16. In the FDA clinical trials, 15 (3%) patients had their inlay removed at 12 months, 36 (7%) at 24 months, and 44 (8%) at 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these three patients underwent concurrent LASIK, which could possibly affect the integrity of the cornea to a greater degree than the creation of a femtosecond tunnel, making them more susceptible to dry eye and infection. It is also possible that the use of preoperative topical antibiotic may help confer a lower postoperative infection rate; Malandrini et al ,18 in their use of the Flexivue Microlens inlay, describe the use of levofloxacin (0.5%) and tobramycin (0.3%)/dexamethasone (0.1%) four times a day for 1 day prior to surgery. It has been suggested that soaking biocompatible implants in antibiotic prior to insertion may help to reduce the incidence of infection and this is common practice in other subspecialties such as with the use of orbital implants 28 29.…”
Section: Discussionmentioning
confidence: 99%